Cavitation sensitivity parameter analysis for centrifugal pumps based on spectral methods - McKee, Kristoffer; Forbes, Gareth; Mazhar, Muhammad Ilyas; Entwistle, Rodney; Hodkiewicz, M.; Howard, Ian (Springer, 2015)
Cavitation is a major problem facing centrifugal pumps in industry today. Unable to constantly maintain operating conditions around the best efficiency point, centrifugal pumps are subject to conditions that may lead to vaporisation or flashing in the pipes upstream of the pump. The implosion of these vapour bubbles in the impeller or volute causes damaging effects to the pump. A new method of cavitation detection is proposed in this paper based on spectral methods. Data used to determine parameters were obtained under ideal conditions, while the method was tested using industry acquired data. Results were compared to knowledge known about the state of the pump, and the classification of the pump according to ISO 10816.